ALT-803, an IL-15 superagonist, in combination with nivolumab in patients with metastatic non-small cell lung cancer: a non-randomised, open-label, phase 1b trial. Issue 5 (May 2018) - Wrangle, John M; Velcheti, Vamsidhar; Patel, Manish R; Garrett-Mayer, Elizabeth; Hill, Elizabeth G; Ravenel, James G; Miller, Jeffrey S; Farhad, Mohammad; Anderton, Kate; Lindsey, Kathryn; Taffaro-Neskey, Michele; Sherman, Carol; et al.
Summary: Background: Immunotherapy with PD-1 or PD-L1 blockade fails to induce a response in about 80% of patients with unselected non-small cell lung cancer (NSCLC), and many of those who do initially respond then develop resistance to treatment. Agonists that target the shared interleukin-2 (IL-2) and IL-15Rβγ pathway have induced complete and durable responses in some cancers, but no studies have been done to assess the safety or efficacy of these agonists in combination with anti-PD-1 immunotherapy. We aimed to define the safety, tolerability, and activity of this drug combination in patients with NSCLC. Methods: In this non-randomised, open-label, phase 1b trial, we enrolled patients (aged ≥18 years) with previously treated histologically or cytologically confirmed stage IIIB or IV NSCLC from three academic hospitals in the USA. Key eligibility criteria included measurable disease, eligibility to receive anti-PD-1 immunotherapy, and an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients received the anti-PD-1 monoclonal antibody nivolumab intravenously at 3 mg/kg (then 240 mg when US Food and Drug Administration [FDA]-approved dosing changed) every 14 days (either as new treatment or continued treatment at the time of disease progression) and the IL-15 superagonist ALT-803 subcutaneously once per week on weeks 1–5 of four 6-week cycles for 6 months. ALT-803 was administered at one of four escalating dose concentrations: 6, 10, 15, or 20 μg/kg. The primary endpoint was to define safety and tolerability and to establish a recommended phase 2 dose of ALT-803 in combination with nivolumab. Analyses were per-protocol and included any patients who received at least one dose of study treatment. This trial is registered withClinicalTrials.gov, numberNCT02523469 ; phase 2 enrolment of patients is ongoing. Findings: Between Jan 18, 2016, and June 28, 2017, 23 patients were enrolled and 21 were treated at four dose levels of ALT-803 in combination with nivolumab. Two patients did not receive treatment because of the development of inter-current illness during enrolment, one patient due to leucopenia and one patient due to pulmonary dysfunction. No dose-limiting toxicities were recorded and the maximum tolerated dose was not reached. The most common adverse events were injection-site reactions (in 19 [90%] of 21 patients) and flu-like symptoms (15 [71%]). The most common grade 3 adverse events, occurring in two patients each, were lymphocytopenia and fatigue. A grade 3 myocardial infarction occurred in one patient. No grade 4 or 5 adverse events were recorded. The recommended phase 2 dose of ALT-803 is 20 μg/kg given once per week subcutaneously in combination with 240 mg intravenous nivolumab every 2 weeks. Interpretation: ALT-803 in combination with nivolumab can be safely administered in an outpatient setting. The promising clinical activity observed with the addition of ALT-803 to the regimen of patients with PD-1 monoclonal antibody relapsed and refractory disease shows evidence of anti-tumour activity for a new class of agents in NSCLC. Funding: Altor BioScience (a NantWorks company), National Institutes of Health, and Medical University of South Carolina Hollings Cancer Center.